A Study on Self-Help Groups (SHG) as a Means of Fostering Development in Developing Countries: with Specific Attention to the Indian Experience - Kaushik, Mridula (Journal of Advanced Research in Public Policy and Administration, 2022)
Self-help groups, often known as SHGs, are playing an increasingly important part in India’s fight against rural poverty in the modern era. The percentage of economically disadvantaged individuals, the majority of whom are women, who are members of self-help groups (SHGs) in various regions of India and who are actively participating in savings (real-term thrift), credit (S/C) and other activities is significant (income generation, natural resources management, literacy, child care and nutrition etc.). The S/C focus is the most conspicuous component of the SHG and it offers a chance to develop some influence over the resources. The SHG system has shown to be both highly necessary and very effective since it gives women the opportunity to progressively free themselves from abusive relationships and social isolation. SHGs in India help assistance from almost all of the main donor organizations, although in a variety of forms. There are a great number of success stories that can be found on the internet that detail how participation in SHG has improved the life of an individual or a whole community. The SHG mechanism is backed by a wide variety of non-governmental organizations (NGOs), who also link it to different other development actions. There is sufficient evidence to suggest that the SHG approach is an extremely dependable, fruitful and pertinent instrument for organizing and motivating common queries; however, the planning, production and implementation of Income Generating Activities (IGAs) programs will generate sufficient, sustainable and long-term revenue (IGAs).